2021
DOI: 10.3389/fpsyt.2021.680403
|View full text |Cite
|
Sign up to set email alerts
|

Between Action and Emotional Survival During the COVID-19 era: Sensorimotor Pathways as Control Systems of Transdiagnostic Anxiety-Related Intolerance to Uncertainty

Abstract: Objectives: The COVID-19 pandemic and aligned social and physical distancing regulations increase the sense of uncertainty, intensifying the risk for psychopathology globally. Anxiety disorders are associated with intolerance to uncertainty. In this review we describe brain circuits and sensorimotor pathways involved in human reactions to uncertainty. We present the healthy mode of coping with uncertainty and discuss deviations from this mode.Methods: Literature search of PubMed and Google Scholar.Results: As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 121 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…Intolerance of uncertainty, or the inability to successfully process and respond to information in uncertain contexts ( 21 , 22 ), was reported to be associated with symptoms of anxiety ( 23 , 24 ). Generally, intolerance of uncertainty is considered to be specific risk factor or cognitive vulnerability in the development and maintenance of anxiety disorders ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intolerance of uncertainty, or the inability to successfully process and respond to information in uncertain contexts ( 21 , 22 ), was reported to be associated with symptoms of anxiety ( 23 , 24 ). Generally, intolerance of uncertainty is considered to be specific risk factor or cognitive vulnerability in the development and maintenance of anxiety disorders ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, inhibiting their responses to the COVID-19 crisis (inhibitory anxiety) had a smaller effect, and one of the potential explanations might be related to the dynamic link between action and emotional survival during the COVID-19 crisis. Nevertheless, there are several other potential explanations that future studies might want to explore, related, for example, to the sensorimotor pathways as control systems of transdiagnostic anxiety through IU ( Goldstein Ferber et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported greater depression and anxiety levels compared to pre-pandemic prevalence of depressive- and anxiety-related syndromes[ 3 , 4 ]. Intolerance to uncertainty has been related to COVID-19 related anxieties due to the inherent uncertainty in the pandemic situation[ 41 ]. In addition, the literature reports on specific pandemic-related psychopathology.…”
Section: The Psychiatric and Neuropsychiatric Reactions To Covid-19 I...mentioning
confidence: 99%